UPAYA PEMERINTAH KOTA TANJUNGPINANG DALAM PELESTARIAN MANGROVE TAHUN 2013 - Fitriady, Muhd Zuhri; Suryadi, Hery (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research was conducted to describe what the Government’s efforts of Tanjungpinang City is, especially for the Department of Marine, Fisheries, Agriculture, Forestry and Energy (KPPKE) and the Environmental Agency (BLH) of Tanjungpinang City for mangrove conservation in Tanjungpinang. Every day mangrove forests in Tanjungpinang City is hoarded by the public due to lack of supervision by Department of Marine, Fisheries, Agriculture, Forestry and Energy (KPPKE) and the Environmental Agency (BLH) of Tanjungpinang. Supposedly, Department of Marine, Fisheries, Agriculture, Forestry and Energy (KPPKE) of Tanjungpinang City is able to provide socialization and cooperation of the Environmental Agency (BLH) of Tanjungpinang which that is the task of the Environmental Agency (BLH) of Tanjungpinang City as supervisor on the environmental pollution’s activities.This research is a descriptive research that using a qualitative approach as a tool of analysis. This research was conducted in Tanjungpinang City, Riau Islands Province. This research was using of some documentation and interviews with key informants and second informants as a second information to achieve the goal in order to get the information of this research. The data that used on this research is primary data and secondary data that is obtained by interviews and documentation directly with key informants and second informants on this research.Lack of the government’s efforts of Tanjungpinang City, the Environment Agency (BLH) and Department of Marine, Fisheries, Agriculture, Forestry and Energy (KPPKE) of Tanjungpinang City for Mangrove conservation in Tanjungpinang City on this research are caused by four factors based on the theory of Edwards III include (a) Communication, both of Tanjungpinang’s government institutions lack of a good communication, so it made less of a good cooperation. (b) Disposition, between the both of Tanjungpinang’s government institutions had less respons about mangrove’s problems, so it considered less responsive. (c) Coordination, between of government’s institutions and the public did not indicate a good coordination and not efficient, so that the hoarding problems continued. (d) Infrastructure, lack of adequate infrastructure, so it made one of the obstacles of good socialization to the public.Keywords: Effort, Mangrove, Tanjungpinang.